Do Gender and BMI Affect the Motor Skills of Five-Year-Old Preschoolers Differently? - Marcos Mecías-Calvo; Fernando Carregal-San Emeterio; Rubén Navarro-Patón (MDPI AG, 2024)
Background/Objective: Weight gain is associated with numerous health complications and constitutes a serious public health problem. Motor competence (MC) can be a protective factor since children's participation and practice in physical activities can improve their health. The objective of this study was to investigate the impact of gender and BMI on MC [i.e., manual dexterity (MD), aiming and catching (A&C), balance (Bal), and total MC percentile (TP)] depending on gender (boy/girl) and BMI (normal weight, overweight or obesity). Methods: The MABC-2 battery was applied in a sample of 368 preschool children (5.69 ± 0.28 years of age; 54.9% girls). Results: Boys and girls showed statistically significant differences in MC components: boys had higher scores in A&C (p = 0.002), while girls excelled in MD (p < 0.001), Bal (p = 0.035); TP (p < 0.001), and BMI [Bal (p = 0.009); TP (p = 0.050)], with a higher percentile in those children with overweight in both cases. Statistically significant differences were also found in the interactions between gender*BMI [MD (p < 0.001) and TP (p < 0.001)]. Conclusions: The findings showed that there were notable variations in total percentile, balance, and manual dexterity between boys and girls. In addition, girls outperformed boys in all categories save aiming and catching. However, males who were overweight or obese earned greater percentiles in both balance and the MABC-2 battery's total percentile.